Trend analysis of precipitation data in flood source areas of Kelantan river basin - Abdulkareem, Jabir Haruna; Sulaiman, Wan Nor Azmin (Penerbit UTM Press, 2016)
Rainfall is one of the most important climatic elements that influence both the spatial and temporal water availability. Therefore, identification of its trend over years is vital for detection of extreme climatic changes. The purpose of this study is to investigate the variability of precipitation in flood source areas of Kelantan river basin by detecting precipitation flood changes in the temporal structure for the period of 1984-2014. A total of 17 rain gage stations with at least 25 years’ records in the temporal structure for the period 1984-2014 were selected. For the AMF data, 4 gauging stations were selected for the analysis. Mann-Kendall and Sen slope estimator tests were used to detect possible precipitation trend. This resulted in the detection of non-statistically significant trend in the annual maximum series of 24-hr precipitation in 12 of the 17 selected rain gauge locations and statistically significant trend in 5 locations for the period under study. Whereas, the AMF series signaled significance at 5% level in all the stations. This may be as a result of watershed characteristics such as land use changes soil, topography, of the study area which needs to be studied in detail.